PENERAPAN METODE REDUKSI VARIABEL DALAM PENGOTIMALAN PENDAPATAN MINIMUM HASIL PRODUKSI BINGKAI FOTO - Safitri, Elfira; Basriati, Sri; Oktavia, Dhea Rizki; Soleh, Mohammad (Universitas Islam Negeri Imam Bonjol Padang, 2024)
Production is an activity that produces an object so that it is more useful in meeting needs. One shop that produces photo frame of various sizes is Terminal Photo Giant. The aim of this research is to determine the minimum income per day from photo frame production using the variable reduction method. The method used in this research is the variable reduction method. The variable reduction method produces an optimal solution with all decision variables in the form of integers without having to branch or add gomory constraints. Based on the result of research using the variable reduction method, Giant Photo Terminal produces a minimum of 4 units of 16 R size photo frames and a minimum of 3 units of 18 R size photo frames every day with a minimum daily income of IDR. 570.000.